Konsep pembangunan jiwa menurut pemikiran Sahl Al-Tustari dalam kitab tafsir Al-Quran Al-Azim: analisis terhadap pemulihan penagihan dadah - Siti Nora’ Aeshah, Zakaria (2024)
Facing drug addiction is a significant challenge because it involves strong physical and psychological dependence. The recovery process requires a strong spirit to keep striving, robust environmental support, and high self-resilience to overcome recurrent addiction. Various efforts have been made by the government to address this issue; however, it often results in relapse. Evidence shows that the relapse rate reaches 40%-50% annually. Recently, there has been a 27% increase in the number of addicts in 2023 compared to 2022. Therefore, this study is conducted with several objectives outlined. The main objective of this study is to analyze the practices adopted by former addicts in their spiritual recovery process based on the concept of spiritual development by Sahl alTustari. The methodology for data collection includes content analysis, interviews, and observations. The researcher analyzes the content using Quraish Shihab's method with the assistance of NVIVO software. The second method used by the researcher is interviewing nine informants who are former addicts that have become operators of private drug rehabilitation centers. The study locations are throughout Malaysia and are determined by research zones, namely the northern, eastern, central, and southern zones. The Borneo zone is not included as there is no information regarding private rehabilitation centers managed by Muslims, except those operated by the church. The main findings of the study aligned with the content analysis findings, emphasizing the thirteen pieces of advice by Sahl al-Tustari to develop the soul in order to sustain resistance against drug addiction, which include obedience, seclusion, supplication to Allah SWT, prayer, remembrance of Allah, choosing friends, seeking knowledge, being close to the Quran, faith, repentance, not despairing, surrendering to Allah, and controlling desires. The findings have been validated with the practices of former drug addicts who have maintained over 15 years without relapse, as they themselves are involved in planning and implementing drug addiction recovery programs in their areas. Based on these study findings, the researcher has developed the Concept of Spiritual Development According to Sahl al-Tustari in drug rehabilitation as the overall summary of the findings. The strength of this concept is that it has been validated by experts from PUSPEN, Harmony Centre, and MUIP. This concept will be proposed to be included in the rehabilitation modules for drug addicts in AADK and rehabilitation centers throughout Malaysia. This concept can also become a part of the corpus of Sufism and Islamic psychology that is taught, discussed, and referenced in various academic studies and spiritual practices throughout the Islamic world.